CHARACTER EDUCATION IN ISLAMIC BOARDING SCHOOL- BASED SMA AMANAH - Abdurrahman, Nana Herdiana (Jurnal Pendidikan Islam, 2016)
This paper aims to describe findings of the study in pesantren-based SMA Amanah covering: 1) the principal policy in developing character education, 2) the methods used in developing character education, 3) studentsâ€™ characteristics as the result of the character education process, 4) the problems encountered in the implementation of character education and the efforts made in addressing the implementation of character education at the school. This study applied qualitative method using descriptive technique. The data were collected through observation, interviews, and documentation. The findings of study showed that: 1) the principalâ€™s policy in developing character education was carried out by implementing government policies in line with the schoolâ€™s vision, mission, and programs; 2) the methods used in the process of character education were through role-modelling, assignments and nurturing, habituation, training programs, andÂ studentsâ€™ participation in various types of activities, as well as the application of rewards and punishments; 3) the student's characteristics resulted from the character Â education process were piousness and devotion as well as being able to apply their knowledge and piety in everyday life; 4) problems encountered in the implementation of character education Â were different values and norms students brought from home; imbalance of facilities compared to the number of students; as well as teachersâ€™ readiness to actually implement the new program, which Â was character education. Meanwhile the efforts made to overcome those problems were namely developing personal, family, neighborhood or community characters, and making commitment of all related parties/stakeholdres of SMA Amanah.